PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP JUMLAH SEL NEURON DI CEREBELLUM Rattus norvegicus BARU LAHIR - Herlina Alvianti N; Hermanto Tri Joewono; widjiati Widjiati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2018)
Efforts could be made to improve humanresources that have intelligence required apositive relationship between health and goodeducation quality, one of the efforts to improvehuman resources requires good brain qualitysince the phase of conception. Classical musichas been shown to boost brain function andhuman intellectual optimally believed to have thebest stimulating effect on babies. Cellularexposure to Mozart affects the number of moreneuronal cells. Analyze the number of cerebrumand cerebellum neuronal cells of newborn Rattusnorvegicus between the exposed to Mozart music,Beethoven, Chopin and not exposed to musicduring pregnancy. This research was anexperimental research with posttest only controlgroup design. The sample was divided into fourgroups randomly, non-exposed, Mozart musicexposure group, Beethoven music exposuregroup, Chopin music exposure group, exposed for1 hour during the night after Rattus norvegicuswas pregnant on day-10 with an intensity of 65 dBand a distance of 37 cm from the rat cage. On the20th day of the pregnant mother of Rattusnorvegicus was sacrificed and selected two ofRattus norvegicus's babies with the greatestweight and then the brains of Rattus norvegicus'sbabies were decapitated and brain dissection tocount the number of neuronal cells withHemotoxyln-Eosin staining. The statistical resultsshowed that the number of neurons of cerebellumcells in the Mozart group differed significantly fromBeethoven, Chopin and not exposed to music withp <0.05. The number of neuronal cells ofcerebellum of the newborn Rattus norvegicus whoexposed to Mozart music during pregnancyproved higher than that exposed to Beethovenmusic, Chopin and not exposed to music.